Role of VDAC1 in hepatocyte apoptosis during acute liver injury in rats induced by obstructive jaundice - Jinshan Liu; Jinlong Hu; Hongyu Xu; Liang Yan; Jiaming Yao; Baoqiang Cao (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): Exploring the role of VDAC1 in hepatocyte apoptosis during acute liver injury induced by obstructive jaundice.Materials and Methods: Animal and cell models were established to investigate possible mechanisms during acute liver injury induced by OJ. Blood was collected for liver function assessment. H&E and TEM were employed to observe pathological changes in the liver tissues. Flow cytometry was used to measure the hepatocyte apoptosis. The mitochondrial MPTP assay was employed to assess the mitochondrial function of hepatocytes. IHC, western blot, and qRT-PCR were employed to determine the expression levels of VDAC1. Then, VDAC-siRNA was used to establish a knockdown model. Flow cytometry was used again to measure hepatocyte apoptosis following VDAC1 knockdown. Results: The serum of rats in the OJ group exhibited a significant increase in liver function. Irregular tissue structure and mitochondrial morphology were observed in the liver tissues of OJ rats. A significant increase in mitochondrial permeability in hepatocytes. The expression levels of VDAC1 were significantly increased in the liver tissue of OJ rats. They were also significantly increased in the hepatocytes, primarily within mitochondrial membranes, determined by western blot in vivo and in vitro. Significant increases in the rates of hepatocyte apoptosis, particularly early apoptosis, were observed in the OJ groups. However, there was a reverse in the rates of hepatocyte apoptosis after knockdown regulation of VDAC1 only within the cells of the OJ group.Conclusion: The up-regulation of VDAC in liver injury caused by obstructive jaundice may lead to increased early apoptosis of hepatocytes.